Official methods of analysis of AOAC international (Oxford, UK Oxford University Press, Inc., 2023)
The Official Methods of Analysis of AOAC INTERNATIONAL is a comprehensive collection of approximately 2,500 validated chemical and microbiological methods and consensus standards related to food, drugs, agriculture, and the environment. This latest edition provides the essential information for the analytical scientists working in relevant fields of chemistry.
List of Changes for the 22nd Edition, 2023 -- Important Notices -- Preface -- About the Association -- Guide to Method Format -- Definition of Terms and Explanatory Notes -- AOAC Official Methods Program -- Standard Method Performance Requirements -- Chapter 1: Agricultural Liming Materials -- Chapter 2: Fertilizers -- Chapter 3: Plants -- Chapter 4: Animal Feed -- Chapter 5: Drugs in Feeds -- Chapter 6: Disinfectants -- Chapter 7: Pesticide Formulations -- Chapter 8: Hazardous Substances -- Chapter 9: Metals and Other Elements at Trace Levels in Foods -- Chapter 10: Pesticide and Industrial Chemical Residues -- Chapter 11: Waters and Salt -- Chapter 12: Microchemical Methods -- Chapter 13: Radioactivity -- Chapter 14: Veterinary Analytical Toxicology -- Chapter 15: Cosmetics -- Chapter 16: Extraneous Materials: Isolation -- Chapter 17: Microbiological Methods -- Chapter 18: Drugs: Part I -- Chapter 19: Drugs: Part II -- Chapter 20: Drugs: Part III -- Chapter 21: Drugs: Part IV -- Chapter 22: Drugs: Part V -- Chapter 23: Drugs and Feed Additives in Animal Tissues -- Chapter 24: Forensic Sciences -- Chapter 25: Baking Powders and Baking Chemicals -- Chapter 26: Distilled Liquors -- Chapter 27: Malt Beverages and Brewing Materials -- Chapter 28: Wines -- Chapter 29: Nonalcoholic Beverages and Concentrates -- Chapter 30: Coffee and Tea -- Chapter 31: Cacao Bean and Its Products -- Chapter 32: Cereal Foods -- Chapter 33: Dairy Products -- Chapter 34: Eggs and Egg Products -- Chapter 35: Fish and Other Marine Products -- Chapter 36: Flavors -- Chapter 37: Fruits and Fruit Products -- Chapter 38: Gelatin, Dessert Preparations, and Mixes -- Chapter 39: Meat and Meat Products -- Chapter 40: Nuts and Nut Products -- Chapter 41: Oils and Fats --Chapter 42: Vegetable Products, Processed -- Chapter 43: Spices and Other Condiments -- Chapter 44: Sugar and Sugar Products -- Chapter 45: Vitamins and Other Nutrients -- Chapter 46: Color Additives -- Chapter 47: Food Additives: Direct -- Chapter 48: Food Additives: Indirect -- Chapter 49: Natural Toxins -- Chapter 50: Infant Formulas, Baby Foods, and Enteral Products -- Chapter 51: Dietary -- Supplements Appendices -- A-R Subject -- Index -- SMPR Index -- Index of Method Numbers.
Keywords: Analytical chemistry -- Laboratory manuals; Agricultural chemistry -- Techniques; Analytical chemistry; Food -- Analysis